Taxonomic study of the Oriental leafhopper genus Kabakra Dworakowska (Hemiptera: Cicadellidae: Typhlocybinae: Erythroneurini), with description of three new species and one new record - Cao, Yanghui; Huang, Min; Zhang, Yalin (Zootaxa, 2012)
Six species of the genus Kabakra Dworakowska were studied and illustrated, including three new species from China and Thailand: Kabakra acutata, K. aviformis, K. celata spp. nov., and one new record from China: Kabakra augusta Dworakowska n. rec.. A key for the identification of adult males is provided.